Multicultural and interreligious perspectives on informed consent. The Christian perspective - Palazzani, Laura (Studia Bioethica, 2019)
The Christian perspective in bioethics, in the framework of a creationistic concept of nature with a normative value (finalism) and in a belief to know the truth in nature (cognitivism), considers human life as worthy of respect and protection (as a gift from God and created in His image), inasmuch as it is the expression of a personal life, dynamically intent on fully manifesting itself. Informed consent acquires a specific meaning in this conceptual framework.